A quick & easy guide to queer & trans identities - G, Mady (Mady M. Giuliani) (Limerence Press, 2019)
"Covering essential topics like sexuality, gender identity, coming out, and navigating relationships, this guide explains the spectrum of human experience through informative comics, interviews, worksheets, and imaginative examples. A great starting point for anyone curious about queer and trans life, and helpful for those already on their own journeys!"--Back cover.